Interference effect of fe on the spectroscopic (faas) determination of au and ag in the ore of İzmit region in Turkey - Ayrancı, Halim; Basak, Ali Sadi; Karabulut, Hakan (Marmara Üniversitesi Fen Bilimleri Dergisi, 2009)
In this paper, interference and matrix effect of Fe on the spectroscopic (FAAS) determination of Au and Ag in the ore of İzmit Region in Turkey was investigated. Au and Ag contents of the samples were determined by the FAAS and Fe by the XRF and found to be about 12.7 % Fe. To determine the interference effect of Fe, standard solutions of FeCl3 were added to 0.5-1 ppm standard solutions of Au increasingly and analyzed by FAAS. The minimum interference occured at 100 ppm Fe3+ in 0.5 ppm standard solution of Au and 500-2000 ppm Fe3+ in 1 ppm standard solution of Au on BC-ON (Background Correction-ON) mode and higher interference ranges were found on BC-OFF mode. As a result, increasing or decreasing the Fe3+ concentration increases the interference ranges remarkably. It has been concluded that the Fe3+ concentration should be optimized for the analysis of Au and Ag in the ore samples containing Fe as well.
Keywords: Interference, Analysis of Au, Digestion, FAAS